2019
DOI: 10.1038/s41598-019-53005-8
|View full text |Cite
|
Sign up to set email alerts
|

Recognition memory reconsolidation requires hippocampal Zif268

Abstract: Object recognition memory (ORM) serves to distinguish familiar items from novel ones. Reconsolidation is the process by which active memories are updated. The hippocampus is engaged in ORM reconsolidation through a mechanism involving induction of long-term potentiation (LTP). The transcription factor Zif268 is essential for hippocampal LTP maintenance and has been frequently associated with memory processes. However, its possible involvement in ORM reconsolidation has not been determined conclusively. Using Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…It has been reported that the memory reconsolidation process involves DNA transcription and de novo protein synthesis ( Nader et al, 2000 ; de la Fuente et al, 2015 ). DNA transcription is regulated by the epigenetic mechanisms of chromatin restructuring and DNA methylation, which play critical roles in the reconsolidation of memory ( Levenson and Sweatt, 2005 ; Duvarci et al, 2008 ; de la Fuente et al, 2015 ; Gonzalez et al, 2019 ; Liu et al, 2022 ). DNMT, a widely expressed DNA methylation enzyme in the mammalian adult nervous system ( Feng et al, 2005 ; Rahn et al, 2013 ), suppresses the transcription process by catalyzing the methylation of cytosine residues in DNA, causing the chromatin structure to compact and abolishing the transcription factors binding to the specific site of DNA ( Miller and Sweatt, 2007 ; Selvakumar et al, 2012 ; Lyko, 2018 ; Shi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the memory reconsolidation process involves DNA transcription and de novo protein synthesis ( Nader et al, 2000 ; de la Fuente et al, 2015 ). DNA transcription is regulated by the epigenetic mechanisms of chromatin restructuring and DNA methylation, which play critical roles in the reconsolidation of memory ( Levenson and Sweatt, 2005 ; Duvarci et al, 2008 ; de la Fuente et al, 2015 ; Gonzalez et al, 2019 ; Liu et al, 2022 ). DNMT, a widely expressed DNA methylation enzyme in the mammalian adult nervous system ( Feng et al, 2005 ; Rahn et al, 2013 ), suppresses the transcription process by catalyzing the methylation of cytosine residues in DNA, causing the chromatin structure to compact and abolishing the transcription factors binding to the specific site of DNA ( Miller and Sweatt, 2007 ; Selvakumar et al, 2012 ; Lyko, 2018 ; Shi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The hippocampus is also necessary for ORM reconsolidation, but only when recall occurs in the presence of a novel object ( 3 ). Indeed, presentation of a novel object during ORM recall activates the reconsolidation marker Zif268 ( 4 ) and is accompanied by a brief depotentiation period followed by a lasting increase in hippocampal synaptic efficacy ( 5 ). Moreover, the amnesia caused by ORM reconsolidation inhibitors is prevented by impairing novelty detection through hippocampal dopamine D1/D5 receptor blockade ( 6 ), suggesting that reconsolidation links the memory of the novel object to the reactivated recognition trace.…”
mentioning
confidence: 99%
“…We presented the PyRAT, a library for animal tracking data analysis developed to be accessible to less experienced programmers. We implemented functions to infer common animal behavioral metrics used in the literature, such as object interaction (duration and number of interactions), traveled distance, speed, and time spent in different areas (Lima et al, 2009 ; Gonzalez et al, 2019 ; Rossato et al, 2019 ; Moura et al, 2020 ). Also, we implemented functions to infer animal behavior from tracked body parts in each frame using unsupervised approaches.…”
Section: Discussionmentioning
confidence: 99%